The Role of Uswah Hasanah in Shaping Students’ Affective Competence in Aqidah and Akhlak Learning at Madrasah Ibtidaiyah - Vivi Afbrifani (Action Research Journal Indonesia (ARJI), 2025)
One of the primary goals of Aqidah Akhlak education for students in Madrasah Ibtidaiyah is the development of the affective domain, which shapes students' attitudes, emotions, and deep religious awareness. This journal article aims to examine the effectiveness of the Uswah Hasanah (exemplary model) method in transforming the values of Aqidah Akhlak into the students' affective domain. The findings reveal that the Uswah Hasanah method, implemented by teachers through exemplary behavior, significantly contributes to shaping students' religious attitudes such as honesty, responsibility, empathy, and discipline. The impact of this method is further strengthened by religious habituation activities, a conducive school culture, and positive interpersonal communication between teachers and students. However, the application of this method also faces obstacles, particularly in the form of teacher behavioral inconsistencies, which may hinder internalization. Therefore, the affective religious development of students should not rely solely on the application of Uswah Hasanah by a single teacher, but rather require collaboration among all educators and the establishment of a holistic religious school culture.